Verbal Clause Construction of Ciacia Language: Syntactic Typology Study - La Yani Konisi; Ketut Artawa; Ni Made Sri Satyawati; I Nyoman Udayana (e-Journal of Linguistics, 2019)
Typology study of Ciacia language (CL) in various linguistic aspects has not beenconducted yet. It is the first study that focus on syntactic typology. Ciacia language is one oflocal languages in Buton Regency, Southeast Sulawesi Province. The study focuses on five mainproblems, they are (1) How is the base construction of verbal clause in CL? (2) How are thepredicate and structure argument constructions of verbal clause in CL, (3) How are the simplepredicate and complex predicate constructions of verbal clause in CL? (4) How are valency andvalency change mechanism of verbal clause construction in CL? (5) How are complex sentenceconstruction and grammatical alliance system?. The oral data of this study is obtained throughrecording and elicitation techniques. Written data is obtained through the previous studies. Thestudy also used synthetic data which is verrified by the informants. The data was analyzed byapportion (distributional) method.The investigation of clause base construction shows that verbal clause construction ofCiacia language is always filled by subject and aspect markers (PS/A) that is affixed to PREDverb. Base structure of verbal clause in CL consists of verbal predicated clause and non-verbalpredicated clause. Non-verbal predicated clause can be constructed through base nominal andadjective categories. Verbal clause predicate can be filled by intransitive base verb, monotransitive base verb, ditransitive base verb, and ambi-transitive base verb.Predication and argument structure of verbal clause construction in CL can be classifiedin to verbal clause: (i) intransitive with one main argument in terms of SUBJ and as A or OBJsystematically; (ii) semi-transitive with one main argument as A/ACT and with the presenceof OBJ argument optionally; (iii) mono-transitive with two main arguments, namely SUBJ asA/ACT with one OBJ argument as UND, (iv) ditransitive with three main arguments, namelySUBJ as A/ACT before PRED and two arguments after PRED, in terms of OTL (indirectobject) and OL (direct object); and (v) ambi-transitive with one main argument, namelySUBJ, either as Sa or as So.Valency and transitivity of verbal clause construction in CL consists of (i) valency andintransitive verb transitivity with one argument or verb with one valency; (ii) semi-transitiveverb with one argument before verb and the presence of argument after Pred verb optionally;(iii) transitive with the obligatory of O presence after Pred verb, so it has two main arguments orverb that has two valency arguments, namely S and O; (iv) ditransitive with three main arguments or verb that has three valency arguments; (v) ambi-transitive with only one argumentor verb that has one valency.Verbal clause construction in CL can be filled by simple Pred verb and complex Predverb. Simple predicate is created by base verb/intransitive verb and non-verb category, semi-transitive verb, and transitive verb with PS/A. Complex predicate is created through verb (i)intransitive; (ii) semi-transitive verb; and (iii) transitive integral verb. The valency changemechanism of verbal clause construction in CL can be done through formal causativation andsemantic causativation, applicative, and resultative.